Digital business for digital entrepreneurs: A review - Hokianto, Hugo Fostin; Fernando, Kisnodi; Herawan, Khenwen; Jaya, Welson; Tiono, Liayanti; Velissia, Lia (BOHR International Journal of Advances in Management Research, 2023)
The era of globalization has affected everyone, including businesses transitioning into electronic devices, and entrepreneurship is going to be digitalized. This means that the world as all people know is changing, and businesses and entrepreneurship skills are going to be transitioned into adapting new technology. This paper discusses five main points, which are defining digital entrepreneurship, the elements and concepts of digital business for digital entrepreneurs, the opportunity for digital business, differences between traditional and digital business, and how to become a digital entrepreneur. This paper uses qualitative descriptive research with a literature review study as its method. The result of the research further gave an insight into what is digital entrepreneurship, the elements and models explained for businesses, opportunities for businesses especially potential sectors that have not been or are soon to be “disrupted” yet, tables of advantages and disadvantages on each type of business, and steps on being a good digital entrepreneur.